Trust dan Perceived Usefulness dan Pengaruhnya Terhadap Preferensi Konsumen Dalam Menggunakan E-wallet - Vania Katherine Hermawan; Eristia Lidia Paramita (STIE Muhammadiyah Jakarta, 2020)
The bloom of banking and fintech companies in Indonesia is marked by the rapid growth of e-wallet users in recent years. The bloom is encouraged by the government by establishing the Gerakan Nasional Non Tunai program to promote cashless society among millennials who are already familiar with cashless lifestyle. There are many factors which attract people to use e-wallet, such as trust, usefulness, and promotion. This research aims to examine the effect of trust and perceived usefulness moderated by the promotion variable on consumers’ preference towards two e-wallet brands—OVO and GoPay. This quantitative research is conducted using Likert scale. The Analysis of Variance (ANOVA) method is used to examine whether each variable has different effect in shaping consumers’ preference. The samples used in this research are active users of OVO and GoPay who are currently living in Semarang. The ANOVA results show that trust, usefulness, and promotion does not have different effect in shaping consumers’ preference. However, they do attract consumers to use e-wallet. This research might be useful to help develop better quality of e-wallet service, security, and utility and build a perfect marketing strategy for banking and fintech companies.